Oral Tuberculosis- A Need For Spy Eye’s - DR.VISHAL MEHROTRA; DR.KRITI GARG; DR.PRIYANKA SHARMA; DR.ROHINI SINGH (International Journal of Pharma and Bio Sciences, 2015)
Tuberculosis is a chronic infectious disease which can affect any part of the body including the mouth. The involvement of oral cavity in tuberculosis is rare and the non specific nature of its clinical presentation makes the diagnosis of tuberculosis delayed. The purpose of this article to emphasize the importance of early diagnosis tuberculosis involving the oral cavity by medical and dental practitioners and considering them in the differential diagnosis of suspicious oral ulcers and thus preventing the morbidity and mortality associated with this life threatening infectious disease.